Design of bluetooth controller for solar grass trimmer - Siti Raudhah, Raduan (2019)
Solar energy is that the heat and light-weight radiations received from the Sun. It is one among the foremost galore types of non-conventional, renewable energy supply found on the world. It is without delay on the market, freed from value and is pollution free. Solar energy is controlled to be become electricity and power by the utilization of devices like star panels that consists of electrical phenomenon cells. Solar system receiving more attention through this year because of its advantages compare to other renewable energy. Solar power is one of the suitable renewable green energy to be used in Malaysia as located in tropical regions and situated near to the equator. Besides, Malaysia is able to receive enough radiation of the light energy from the sunlight to generate electricity. The demand and request for green energy technology produced by renewable energy sources has increased. The objective of this project is to control all the movement and the direction of the trimmer by using an application in the PlayStore. Therefore, the application needs to connect with a Bluetooth device that connected with all the electrical components in the electrical box. So, it will be come up with the trimmer that is transportable, durable, easy to operate and maintain. The advantage of powering a grass trimmer by solar instead of by fuel is principally ecological. It additionally aims to style an Android-hopped-up trimmer of electrical source which a conductor electric grass lawn tool. The heart of the machine may be a battery hopped-up DC motor. It is additionally helpful technique for our grass trimmer. The present technology usually used for trimming the grass is by exploitation the manually handle device. The Bluetooth-driven the machine for trimming the grass is applied. The device consists of blade that is operated with the assistance of the motor. The battery will then be charge by the solar. Meanwhile, the solar grass trimmer can be operated anywhere within the Bluetooth signal range by the mobile phone of the owner.